Analisis Manajemen Pemasaran Pada UMKM (Studi Usaha Jahit HANIMIST) - Alhaini Mistlaiha Annur; Kasful Anwar (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2021)
Marketing strategy is one of the activities or ways that can increase the advantage of a business in order to increase the profit of a business. Marketing is important to do because from here we can determine how to publish our product or business to consumers so that consumers are interested in buying or using our services. There are several media that can be used to market a product or service, such as social media, which is now a marketing alternative for millennials. Now there are many interesting and unique new businesses that can steal the attention, with that the increasingly difficult or increasingly fierce business competition. Moreover, there are many sewing service businesses that are older and more trustworthy than new businesses that will develop. There are many marketing strategies that must be considered in starting and running a business. This study aims to get an overview or find out what kind of marketing strategy is carried out by MSME businesses that are just starting to develop their businesses, and how effective these strategies are.